Effect of glucose on chlorella vulgaris in heterotrophic culture - Angie, Sapis (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Microalgae, Chlorella vulgaris, can be cultivated heterotrophically with the supplementation of glucose as their main carbon source. The aim of this study is to cultivate UNIMAS culture collection of green algae, C. vulgaris, in Modified Bristol’s Media (MBM). Different factors such as different glucose concentrations and initial pH level were tested in affecting the cell growth in the heterotrophic culture. The microalgae was cultured at 25°C and pH 7.16 for first treatment and pH 9.11 for second treatment, and 12 days in dark. Higher growth performance was observed on day 8 to 10, in both treatments respectively. This experiment revealed that autotrophic Chlorella species microalgae can grow better in glucose heterotrophically